Ready to learn from your students? Chinese undergraduate students' experiences of informal reverse mentoring - Yanjuan Hu; Zixi Zhou (Future in Educational Research)
Abstract This study explores the potential of reverse mentoring as a way to renew the student–supervisor relationship in the Chinese higher education setting. We interviewed 17 Chinese undergraduates who engaged in informal reverse mentoring with their supervisors while working on undergraduate research projects. The findings reveal the existence of informal reverse mentoring dynamics between Chinese undergraduate students and their supervisors in three specific areas: (1) students provide fresh perspectives and expand their supervisors' ideas; (2) students actively introduce new research tools and techniques to their supervisors; and (3) students challenge their supervisors' viewpoints, including identifying their mistakes. Our study also shows that informal reverse mentoring benefits supervisors primarily through enhanced professional development and benefits students through increased sense of fulfillment, self‐confidence, and engagement. The analysis further identifies several personal and contextual factors that influence the practice of informal reverse mentoring. We also discuss the potential of (informal) reverse mentoring as a tool for intergenerational learning and the key role of the supervisor as a change agent to innovate their interaction style with Generation Z students.